Implantação de uma middleware IoT escalável para aplicações de mobilidade elétrica multimodal. - LOBATO, Elen Priscila de Souza (Universidade Federal do Pará, 2024)
This work will present the implementation of the Dojot platform in a scalable and customized way, such as the Internet of Things (IoT) middleware of a Research and Development (R&D) Project of Multimodal Electric Mobility in the Amazon Region. Two environments were implemented with Dojot, being a development environment with Docker Compose, in only one machine, and a production environment in a Kubernetes cluster, with a master machine, two worker machines and a load balancer. To verify the consumption of CPU and memory metrics, in both environments, simulations were performed of several electric mobility devices receiving data simultaneously in Dojot. Thus, it was observed that there was a lower CPU consumption in the development environment, lower memory consumption in the production environment and the environment that best responded to the scalability issue (with the increase in the number of devices receiving data) was production. In conclusion, the implementation of Dojot in the production environment, in a Kubernetes cluster, is more advantageous in terms of scalability